Aliarcobacter, Halarcobacter, Malaciobacter, Pseudarcobacter and Poseidonibacter are later synonyms of Arcobacter: transfer of Poseidonibacter parvus, Poseidonibacter antarcticus, 'Halarcobacter arenosus', and 'Aliarcobacter vitoriensis' to Arcobacter as Arcobacter parvus comb. nov., Arcobacter antarcticus comb. nov., Arcobacter arenosus comb. nov. and Arcobacter vitoriensis comb. nov. Issue 11 (26th November 2021) - On, Stephen L. W.; Miller, William G.; Biggs, Patrick J.; Cornelius, Angela J.; Vandamme, Peter
Abstract : This paper re-examines the taxonomic positions of recently described Poseidonibacter ( P. parvum and P. antarcticus ), Aliarcobacter (' Al. vitoriensis' ), Halarcobacter (' H. arenosus ') and Arcobacter ( A. caeni, A. lacus ) species, and other species proposed to represent novel genera highly related to the genus Arcobacter . Phylogenomic and several overall genome relatedness indices (OGRIs) were applied to a total of 118 representative genomes for this purpose. Phylogenomic analyses demonstrated the Arcobacter clade to be distinct from other Epsilonproteobacteria, clearly defined and containing closely related species. Aliarcobacter butzleri and Malaciobacter pacificus did not cluster with other members of these proposed genera, indicating incoherence of these genera. Every OGRI measure applied indicated a high level of relatedness among all Arcobacter clade species, including the recently described taxa studied here, and substantially lower between type species representatives for other Epsilonproteobacteria. Where published guidelines were available, OGRI values for Arcobacter clade species were either unsupportive of division into other genera or were at the lowest boundary range (for average amino acid identity). We propose that Aliarcobacter, Halarcobacter, Malaciobacter, Pseudarcobacter, Poseidonibacter and Arcobacter sensu stricto be considered members of a single genus, Arcobacter, and subsequently transfer P. parvum, P. antarcticus, ' Al. vitoriensis ' and ' H. arenosus ' to Arcobacter as Arcobacter parvum comb. nov., Arcobacter antarcticus comb. nov., Arcobacter vitoriensis comb. nov. and Arcobacter arenosus comb. nov.